In vitro studies on anti-inflammatory activities of kiwifruit peel extract in human THP-1 monocytes. (6th April 2019) - D'Eliseo, Donatella; Pannucci, Elisa; Bernini, Roberta; Campo, Margherita; Romani, Annalisa; Santi, Luca; Velotti, Francesca
Abstract: Ethnopharmacological relevance: Kiwifruit is native to eastern China and many are the references about the consumption of fruits and fruits extracts of the Actinidia plants in Chinese traditional medicine as therapeutic food supplements to prevent and/or counteract numerous disorders including inflammation-related diseases like cancer. Aim of the study: Aim of the present work was to obtain a kiwifruit peel extract, rich in polyphenols, and to explore the anti-inflammatory potential by analyzing its capability to target multiple pathways involved in monocyte-mediated inflammatory response. Materials and methods: The extract was obtained from the fruit peel of Actinidia deliciosa (A.Chev.) C.F.Liang & A.R.Ferguson, cv Hayward and characterized by HPLC-DAD-ESI-MS. Lipopolysaccharide-stimulated THP-1 monocytes were used as a model of human inflammation in vitro . Results: Analytical data evidenced that procyanidins resulted the main polyphenols present in the extract, representing the 92% w/w of the total. The extract inhibited the production of inflammatory molecules such as IL-6, IL-1β, TNF-α pro-inflammatory cytokines, HMGB1 danger signal and granzyme B serine protease by activated monocytes. In particular, an inhibitory activity of 81%, 68%, 63%, 76% and 60% on the extracellular release of IL-6, IL-1β, TNF-α, HMGB1 and granzyme B, respectively, was observed by western blot analysis. Moreover, the extract prevented STAT3 activation and promoted autophagy. Conclusions: The reported findings demonstrated a strong and broad anti-inflammatory profile of the kiwifruit peel extract, which makes it a promising preventive and therapeutic natural ingredient for nutraceutical, cosmetic and pharmaceutical formulations to counteract multiple inflammatory disorders. Graphical abstract: fx1